2020
DOI: 10.1111/psyg.12600
|View full text |Cite
|
Sign up to set email alerts
|

Personality and health literacy among community‐dwelling older adults living in Japan

Abstract: Background: Previous studies have demonstrated that health behaviours may be one of the major mechanisms underlying the relationship between personality and health outcomes. Such health behaviours may be established by consciousness toward one's health that include health literacy. Thus, this study aimed to explore the relationship between health literacy and its correlates, including personality, among community-dwelling older adults. Methods: This was a cross-sectional study with 683 older individuals (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
(114 reference statements)
1
18
0
Order By: Relevance
“…Furthermore, this tendency is closely related to health literacy [ 41 ]. Openness is also closely correlated to health literacy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this tendency is closely related to health literacy [ 41 ]. Openness is also closely correlated to health literacy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy can be an independent factor influencing health outcomes. Those with a low level of health literacy are related to poor health outcomes such as insufficient use of healthcare services, high hospitalization rates, and high mortality rates according to some studies ( DeWalt et al, 2004 ; Baker et al, 2007 ; Huang et al, 2017 ; Iwasa and Yoshida, 2020 ). In addition, it is difficult for people with low health literacy to update their health knowledge or obtain the best medical advice from health experts to change their health-related lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that socioeconomic status (SES) had closely links to health literacy ( Adler and Newman, 2002 ; Bonaccorsi et al, 2019 ). SES may become a predictor of health literacy ( Iwasa and Yoshida, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that these personality traits have been shown to predict multiple health risk factors that are related to homebound status [ 13 , 14 ]. In terms of physical health, personality traits were associated with functional ability [ 15 ], cognitive decline, chronic diseases [ 16 ], and pain [ 17 , 18 ]. For example, evidence suggests that older adults with low conscientiousness and high neuroticism tended to engage in fewer physical activities [ 19 ], have poorer physical function [ 20 ], higher risk of falling [ 21 ] and frailty [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of mental health, personality traits were associated with depression and anxiety. For instance, older adults with high neuroticism were more likely to experience negative emotions and present depressive symptoms [ 16 , 18 , 25 , 26 ]. Lower extraversion and conscientiousness were significantly associated with the presence and severity of depression [ 27 ].…”
Section: Introductionmentioning
confidence: 99%